African American couple posed in front of the Cyclone Racer, Long Beach, CA, July 1949. (1949)
Downtown Long Beach provided delegates with sightseeing opportunities including the beachside amusement park called The Pike featuring a large wooden roller coaster, the Cyclone Racer